Analisis Manajemen Modal Kerja UMKM di Kota Mataram - Iwan Kusmayadi; Baiq Nurul Suryawati; Laila Wardani (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2019)
The focus of this study is to determine the effectiveness of working capital management in UMKM in the city of Mataram. Based on data from the Office of Cooperatives and UMKM in Mataram, the number of UMKM was recorded as 130 UMKM with various types of businesses, by determining the number of samples of 13 UMKM with variations in comparison of sales turnover and expenditure of more than 50% according to data issued by the Mataram City Cooperative and UMKM Office . The results of the study of the management of UMKM working capital in the city of Mataram showed that the amount of working capital grew even though at a low level. Management of working capital in UMKM in Mataram city in general can still be said to be ineffective, being in an overlapping position over the past three years which indicates too much unemployed funds which have an impact on declining profit growth. Fostering small businesses by related agencies, tertiary institutions and LSM needs to be raised to reduce problems experienced by small businesses, especially capital assistance, business management, production and marketing techniques.